Swedish experts' understanding of active aging from a culturally sensitive perspective – a Delphi study of organizational implementation thresholds and ways of development - Johansson, Carl; Lindberg, Daniel; Morell, Ildikó Asztalos; Gustafsson, Lena-Karin (Frontiers in Sociology, 2022)
Background International migration and aging populations make for important trends, challenging elderly care regimes in an increasingly globalized world. The situation calls for new ways of merging active aging strategy and cultural sensitivity. This study aim to illuminate the gap between cultural sensitivity and active aging to identify perceived thresholds by Swedish municipal officials in the understanding of older late-in-life-immigrants situation. Methods Delphi methodology in three rounds. Twenty-three persons in municipal decision-making positions participated and generated 71 statements, of which 33 statements found consensus. Results The 33 statements show that the decision makers prefer not to use cultural sensitivity as a concept in their work, but rather tailor interventions based on individual preferences that may or may not be present in a certain culture. However, as the complexity of care increases, emphasis drifts away from personal preferences toward text-book knowledge on cultures and activity.